2006
DOI: 10.1001/archneur.63.10.1402
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 Fatty Acid Treatment in 174 Patients With Mild to Moderate Alzheimer Disease: OmegAD Study

Abstract: Background: Epidemiologic and animal studies have suggested that dietary fish or fish oil rich in-3 fatty acids, for example, docosahexaenoic acid and eicosapentaenoic acid, may prevent Alzheimer disease (AD). Objective: To determine effects of dietary-3 fatty acid supplementation on cognitive functions in patients with mild to moderate AD. Design: Randomized, double-blind, placebo-controlled clinical trial. Participants: Two hundred four patients with AD (age range [mean±SD], 74 ± 9 years) whose conditions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
484
2
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 680 publications
(516 citation statements)
references
References 27 publications
21
484
2
9
Order By: Relevance
“…4 Positive effects were, however, observed in a subgroup of patients with very mild AD (Mini Mental State Examination 427 points) in another clinical trial. 27 The vascular risk factors hypertension, obesity, hyperlipidemia, diabetes and smoking were not associated with the risk of AD in this cohort. In the subjects with higher proportions of saturated FAs, however, the AD risk was actually lower.…”
Section: Discussionmentioning
confidence: 62%
“…4 Positive effects were, however, observed in a subgroup of patients with very mild AD (Mini Mental State Examination 427 points) in another clinical trial. 27 The vascular risk factors hypertension, obesity, hyperlipidemia, diabetes and smoking were not associated with the risk of AD in this cohort. In the subjects with higher proportions of saturated FAs, however, the AD risk was actually lower.…”
Section: Discussionmentioning
confidence: 62%
“…It has been further proposed by epidemiological studies in humans that UFA, provided e.g., by olive oil and sea-fish in the traditional mediterranean diet, exert a risk-lowering effect for AD and cognitive impairment (22)(23)(24)(25)(26)(27). Recently, 2 interventional studies reported a significant cognitive improvement in patients suffering from mild cognitive impairment (MCI) after intake of omega-3 polyUFA supplements vs. placebo (28,29). However, inconclusive or negative findings from animal and observational studies have also been reported for CR (e.g., 30,31,32) and UFAs (33,34).…”
mentioning
confidence: 99%
“…By contrast, a separate meta-analysis by the APA's reviewers of four trials involving schizophrenia patients showed no overall benefits for psychotic symptoms, although it was noted that an increased intake of n-3 fatty acids might help to combat the increased risks of CVD, diabetes and other physical health problems associated with this illness, which are exacerbated by some antipsychotic medications. Some benefits for mood, impulsivity, stress-aggression and other aspects of behaviour or cognition have also been reported in psychiatrically normal populations 8,9 , children with attention-deficit hyperactivity disorder and related conditions 10 , and patients with mild dementia 11 , although findings in these areas remain preliminary or mixed, and most studies have been small. This new study by Rogers and colleagues 4 set out to investigate whether n-3 fatty acid supplementation could improve mental health in a sample more representative of the general population.…”
mentioning
confidence: 98%